Tropical Pacific relationships with Southern Hemisphere atmospheric circulation and Antarctic climate - Kyle Clem (8513082) (2017)
Significant trends in high-latitude Southern Hemisphere atmospheric circulation and surface climate have been observed over recent decades, which are likely linked to teleconnections from the tropics. This study investigates how a recent shift in tropical Pacific climate toward increased La Niña conditions has influenced the atmospheric circulation and surface climate across the high southern latitudes, and how variations in the El Niño-Southern Oscillation (ENSO) and Southern Annular Mode (SAM) influence the surface climate of Antarctica. Over 1979-2014, significant cooling of eastern tropical Pacific sea surface temperatures (SSTs) is detected in all seasons. The eastern tropical Pacific cooling is associated with: (1) an intensified Walker Circulation during austral summer and autumn; (2) a weakened South Pacific Hadley cell and sub-tropical jet during autumn; and (3) a strengthening of the circumpolar westerlies between 50 and 60°S during both summer and autumn. Observed cooling in the eastern tropical Pacific is linearly congruent with 60-80% of the observed positive zonal-mean zonal wind trend between 50 and 60°S during summer (~35% of the interannual variability), and around half of the positive zonal-mean zonal wind trend during autumn (~15% of the interannual variability), the latter being most marked over the South Pacific. Although previous studies have linked the strengthening of the tropospheric westerlies during summer and autumn to ozone depletion, results from this study indicate poleward momentum fluxes and strengthened lower-tropospheric baroclinicity associated with eastern tropical Pacific cooling also help to maintain a strengthened mid-latitude jet through the 21st century, especially across the South Pacific. The La Niña shift in tropical Pacific SSTs is also significantly related to several changes in Antarctic surface climate. During autumn, a regional pattern of cooling occurred along coastal East Antarctica after 1979, with the rate of cooling increasing at Novolazarevskaya, Syowa, Casey, and Dumont d’Urville stations, while the rate of cooling decreased at Mawson and Davis stations. It is shown that regional circulation changes associated with tropical Pacific teleconnections project strongly onto the regional nature of the cooling trends, with 40% of the cooling at Novolazarevskaya and Syowa linearly congruent with the increased La Niña conditions, and more than 60% of the cooling at Casey and Dumont d’Urville linearly congruent with increased SSTs over the western tropical Pacific. The autumn La Niña pattern is associated with an anomalous anticyclone over the high-latitude South Atlantic that strengthens southwesterly winds and cold air advection across Novolazarevskaya and Syowa. Meanwhile, warming over the western tropical Pacific is associated with a meridional wavetrain stretching from southwest Australia to eastern East Antarctica and anomalous poleward momentum fluxes that locally strengthen westerly / southwesterly winds along and offshore of Casey and Dumont d’Urville, amplifying the cooling seen there. During spring, a physical mechanism linking the West Antarctic warming to the tropical Pacific is identified. Spring warming of West Antarctica and the Antarctic Peninsula is associated with a significant increase in tropical deep convection on the poleward side of the South Pacific Convergence Zone. The increase in deep convection is strongest during September, during which a meridional wavetrain is seen over the western South Pacific with anomalous cyclonic circulation over the Ross Sea and warm, northerly flow to western West Antarctica. During October, the wavetrain propagates east toward the Antarctic Peninsula as the climatological background westerlies strengthen, which leads to increased warm, northerly flow to the western Antarctic Peninsula. Observed increases in deep convection along the South Pacific Convergence Zone during September are linearly congruent with over half of the observed circulation and surface warming trends seen across the West Antarctic region during September and October. Lastly, this study finds a spatial dependency of the ENSO and SAM impact on Antarctic Peninsula climate. Variability in ENSO has a persistent and statistically significant relationship with western Peninsula climate only, which is strongest during the winter and spring seasons. Meanwhile, variability in the SAM dominates climate across the northeastern Peninsula during all seasons through the Föhn effect, and northeast Peninsula relationships with the tropics are relatively weak. In autumn, when widespread warming of the Antarctic Peninsula has been linked to the tropics, this study finds the tropical connection to be weak and statistically insignificant on interannual timescales, and regional circulation associated with the SAM dominates climate variability across the Peninsula during autumn.